1995
DOI: 10.1002/tcm.1770150404
|View full text |Cite
|
Sign up to set email alerts
|

Cyclophosphamide‐induced teratogenesis in ICR mice: The role of apoptosis

Abstract: It is known that programmed cell death (apoptosis) is an important physiological determinant of embryonic development. In parallel, it may be one of the major events involved in induced teratogenesis. The present study was designated to evaluate to what extent is apoptosis involved in the formation of some final abnormalities induced by cyclophosphamide (CP) in ICR mice. The level of apoptosis in limbs, tail, liver, and whole embryo was assessed 24 h after administration of various doses of CP (day 12 of pregn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 15 publications
1
38
0
Order By: Relevance
“…A body of studies suggests that the pathogenesis of CP-induced developmental structural anomalies includes intermediate steps such as excessive apoptosis and suppression of cell proliferation (Chernoff et al 1989, Francis et al 1990, Little & Mirkes 1992, Torchinsky et al 1995a. In this work, CP-induced apoptosis was evaluated by the TUNEL assay and by measuring the levels of active caspases 3, 8, and 9.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A body of studies suggests that the pathogenesis of CP-induced developmental structural anomalies includes intermediate steps such as excessive apoptosis and suppression of cell proliferation (Chernoff et al 1989, Francis et al 1990, Little & Mirkes 1992, Torchinsky et al 1995a. In this work, CP-induced apoptosis was evaluated by the TUNEL assay and by measuring the levels of active caspases 3, 8, and 9.…”
Section: Discussionmentioning
confidence: 99%
“…The choice of the brain was based on our previous studies (Torchinsky et al 1995a) suggesting that the intensity of CP-induced apoptosis in this organ directly correlates with the incidence (or severity) of nearly all CP-induced structural anomalies tested in the study. As to the limbs, they were chosen because in this study the limbs of p53 knockout and wild-type embryos were found to differ dramatically in the sensitivity to CP-induced teratogenic insult.…”
Section: Teratological Testingmentioning
confidence: 99%
“…at 8:00 AM on day 12 of pregnancy at a dose of 40 mg/kg (in 0.5 ml saline per 20 g body weight). The results of previous studies [3,4,13] indicated that this dose of CP will affect all tested embryonic organs in all embryos.…”
Section: Materials and Methods Animal Modelmentioning
confidence: 92%
“…We have shown that in litters of mice treated with a dose of 40 mg/kg of cyclophosphamide (CP) and tested on day 19 of pregnancy, all fetuses had craniofacial (agnathia, exencephaly, cleft palate, open eyes), limb reduction anomalies (amelia or phocomelia), and severe growth retardation [3]. In parallel, it has been observed [4] that this dose of CP initiates apoptosis in the limbs, head, and liver of murine embryos 24 h after CP administration and that limb reduction and craniofacial anomalies are clearly seen by 48 h after CP treatment. The liver, however, did not differ macroscopically from that of control embryos either at this time point or 24 h later.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation